The Effects of Different Curing Methods on the Compressive Strength of Terracrete - J. A. Ayangade; O. Alake; A. B. Wahab (Civil Engineering Dimension, 2009)
This research evaluated the effects of different curing methods on the compressive strength of terracrete. Several tests that included sieve analysis were carried out on constituents of terracrete (granite and laterite) to determine their particle size distribution and performance criteria tests to determine compressive strength of terracrete cubes for 7 to 35 days of curing. Sand, foam-soaked, tank and open methods of curing were used and the study was carried out under controlled temperature. Sixty cubes of 100 × 100 × 100mm sized cubes were cast using a mix ratio of 1 part of cement, 1½ part of latrite, and 3 part of coarse aggregate (granite) proportioned by weight and water – cement ratio of 0.62. The result of the various compressive strengths of the cubes showed that out of the four curing methods, open method of curing was the best because the cubes gained the highest average compressive strength of 10.3N/mm2 by the 35th day.